In vitro readthrough of termination codons by gentamycin in the Stüve–Wiedemann Syndrome - Bellais, Samuel (Nature Publishing Group, 2010)
The Stüve–Wiedemann Syndrome (SWS) is a frequently lethal chondrodysplasia caused by null mutations in the leukemia inhibitory factor receptor gene (LIFR) responsible for an impaired activation of the JAK–STAT pathway after LIF stimulation. Most LIFR mutations are nonsense mutations, thus prompting us to investigate the impact of aminoglycosides on the readthrough of premature termination codons (PTCs). Culturing skin fibroblasts from three SWS patients and controls for 48 h in the presence of gentamycin (200–500 μg/ml) partially restored the JAK–STAT3 pathway when stimulated by LIF. Consistently, quantitative RT-PCR analysis showed that gentamycin stabilized LIFR mRNAs carrying UGA premature termination codons. We conclude that high gentamycin concentrations can partially restore functional LIFR protein synthesis in vitro, prompting us to investigate PTC readthrough using less toxic and more efficient drugs in this presently untreatable lethal condition.